The ESL/ELL teacher's survival guide ready-to- use strategies, tools, and activities for teaching English language learners of all levels - Ferlazzo, Larry; Hull-Sypnieski, Katie 1974- (Hoboken, New Jersey John Wiley & Sons, Inc., 2022)
"The ESL/ELL Teacher's Survival Guide, 2nd Edition offers educators practical strategies for setting up an ESL-friendly classroom, motivating and interacting with students, communicating with parents of English language learners, and navigating the challenges inherent in teaching ESL students. The second edition includes more than 150 pages of new content, including: A new chapter on working with Long-Term English Language Learners A new chapter on teaching English to students in countries where English is not the primary language A new chapter on Teaching Elementary Age ELLs An updated chapter on Math An updated chapter on Science Revised connections to Common Core Standards Updated research & technology connections Many new instructional strategies and student hand-outs that we were not able to include in The ELL Teacher's Toolbox, including sections on assessment, homework, the summer slide and many more"--Provided by publisher.
ELL instruction: the big picture -- ELL classroom basics: building a positive and effective learning environment -- Key elements of a curriculum for beginning ELLs -- Daily instruction for beginning ELLs -- Key elements of a curriculum for intermediate ELLs -- Daily instruction for intermediate ELLs -- English language learners in the mainstream classroom -- Teaching social studies -- Teaching science -- Teaching math -- Supporting long-term English language learners -- Working with Elementary ELLs -- Teaching adult ELLs -- Teaching ELLs with learning differences -- Culturally responsive and sustaining teaching -- Addressing additional opportunities and challenges -- Home language of ELLs -- Using learning games in the ELL classroom -- Assessing English Language Learners -- Reflective teaching/Professional development.
Includes bibliographical references (pages 499-537) and index.
Keywords: English language -- Study and teaching -- Foreign speakers